Value evaluation method of industrial product-service based on customer perception. (2018) - Wang, P.P.; Ming, X.G.
It has become an important trend in the manufacturing industry that service is used to enhance the competitiveness of businesses as well as an important source of values. Aiming to realise the performance evaluation of industrial product-service and lay a basis for further development and application of industrial product-service systems, a value evaluation method based on customer perception is presented in this paper. First, performance evaluation index system of industrial product-service is proposed based on product-service value properties. The performance evaluation method is developed based on ordered weighted averaging operator of fuzzy language. Second, ability evaluation index system of service value creation is proposed based on value demands of customers. And the ability evaluation method is developed based on fuzzy synthetic and hierarchy analysis. Finally, the proposed approach to product-service value evaluation is demonstrated by an example of automobile marketing service from XX 4S shop.